Thermodynamic Integration in 3n Dimensions Without Biases or Alchemy for Protein Interactions - Chen, Liao Y. (Frontiers in Physics, 2020)
Thermodynamic integration (TI), a powerful formalism for computing Gibbs free energy, has been implemented for many biophysical processes with alchemical schemes that require delicate human efforts to choose/design biasing potentials for sampling the desired biophysical events and to remove their artifactitious consequences afterwards. Theoretically, an alchemical scheme is exact but practically, an unsophisticated implementation of this exact formula can cause error amplifications. Small relative errors in the input parameters can be amplified many times in their propagation into the computed free energy [due to subtraction of similar numbers such as (105±5)−(100±5) = 5±7]. In this paper, we present an unsophisticated implementation of TI in 3n dimensions (3nD) (n = 1, 2, 3…) for the potential of mean force along a 3nD path connecting one state in the bound state ensemble to one state in the unbound state ensemble. Fluctuations in these 3nD are integrated in the bound and unbound state ensembles but not along the 3nD path. Using TI3nD, we computed the standard binding free energies of three protein complexes: trometamol in Salmonella effector SpvD (n = 1), biotin-avidin (n = 2), and Colicin E9 endonuclease with cognate immunity protein Im9 (n = 3). We employed three different protocols in three independent computations of E9-Im9 to show TI3nD's robustness. We also computed the hydration energies of 10 biologically relevant compounds (n = 1 for water, acetamide, urea, glycerol, trometamol, ammonium and n = 2 for erythritol, 1,3-propanediol, xylitol, biotin). Each of the 15 computations is accomplishable within 1 (for hydration) to 10 (for E9-Im9) days on an inexpensive GPU workstation. The computed results all agree with the available experimental data.